Pengaruh Beban Kerja dan Stres Kerja Terhadap Kinerja Karyawan di PT BCA Multifinance - Mitra Ananda Ginting; Ranthy Pancasasti (GEMILANG: Jurnal Manajemen dan Strategi Bisnis, 2022)
The purpose of the study was to test and analyze the effect of workload and work stress on employee performance. The object of the research was conducted at PT Bank BCA Multifinance with the number of samples taken as many as 90 people. The data collection method used a questionnaire which was then analyzed using the SEM-PLS model which was processed with the SmartPLS application. Based on the results of statistical tests, it is known that there is no effect of workload on employee performance. There is a significant effect of work stress on employee performance. This study found that work stress can affect employee performance, so good management of work stress is needed from management so that employees can still improve their performance even though they are under pressure.